Preliminary validation of FastaReada as a measure of reading fluency - Elhassan, Zena; Crewther, Sheila G.; Bavin, Edith L.; Crewther, David P. (Frontiers in Psychology, 2015)
Fluent reading is characterized by speed and accuracy in the decoding and comprehension of connected text. Although a variety of measures are available for the assessment of reading skills most tests do not evaluate rate of text recognition as reflected in fluent reading. Here we evaluate FastaReada, a customized computer-generated task that was developed to address some of the limitations of currently available measures of reading skills. FastaReada provides a rapid assessment of reading fluency quantified as words read per minute for connected, meaningful text. To test the criterion validity of FastaReada, 124 mainstream school children with typical sensory, mental and motor development were assessed. Performance on FastaReada was correlated with the established Neale Analysis of Reading Ability (NARA) measures of text reading accuracy, rate and comprehension, and common single word measures of pseudoword (non-word) reading, phonetic decoding, phonological awareness and mode of word decoding (i.e., visual or eidetic versus auditory or phonetic). The results demonstrated strong positive correlations between FastaReada performance and NARA reading rate (r = .75), accuracy (r = .83) and comprehension (r = .63) scores providing evidence for criterion-related validity. Additional evidence for criterion validity was demonstrated through strong positive correlations between FastaReada and both single word eidetic (r = .81) and phonetic decoding skills (r = .68). The results also demonstrated FastaReada to be a stronger predictor of eidetic decoding than the NARA rate measure, with FastaReada predicting 14.4% of the variance compared to 2.6% predicted by NARA rate. FastaReada was therefore deemed to be a valid tool for educators, clinicians, and research related assessment of reading accuracy and rate. As expected, analysis with hierarchical regressions also highlighted the closer relationship of fluent reading to rapid visual word recognition than to phonological-based skills. Eidetic decoding was the strongest predictor of FastaReada performance (16.8%) followed by phonetic decoding skill (1.7%). Phonological awareness did not make a unique contribution after eidetic decoding and phonetic decoding skills were accounted for.